2017
DOI: 10.1007/s13595-017-0661-y
|View full text |Cite
|
Sign up to set email alerts
|

Understanding biological characteristics of Acacia melanoxylon in relation to fire to implement control measurements

Abstract: & Key message Acacia melanoxylon produces abundant seeds leading to large seed banks in the soil. These seeds display a large viability and their germination is stimulated by heat. To control the populations, it is necessary to remove adults and young individuals, and to prevent seedling establishment after fire occupying the space with rapid growth and high competitive native species. & Context Acacia melanoxylon displays a widespread distribution in South West Europe, and an improved knowledge of its reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Scarified seeds of C. scoparius were subjected to a solution of 2,3,3-triphenyl tetrazolium chloride salt at 1%. Five replicates, of 25 seeds each, were made [29,38]. The seeds were kept in the solution for 48 h in the dark and then all tincted seeds were recorded as live seeds.…”
Section: Viability and Germinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Scarified seeds of C. scoparius were subjected to a solution of 2,3,3-triphenyl tetrazolium chloride salt at 1%. Five replicates, of 25 seeds each, were made [29,38]. The seeds were kept in the solution for 48 h in the dark and then all tincted seeds were recorded as live seeds.…”
Section: Viability and Germinationmentioning
confidence: 99%
“…Fire severity, through combustion or lethal heating during burning, directly determines the availability of post-fire in situ propagules generated [90]; however, it can also lead to greater recruitment of seedlings and resprouts [12,38] and, likely, this affects the natural regeneration of communities. Our results showed that the germination behaviour of C. scoparius and S. atrocinerea were strongly influenced by certain fire factors.…”
Section: Fire Factors Effectsmentioning
confidence: 99%
“…Fire and summer temperatures work together breaking seed dormancy (Luna 2020), opening the possibility for new species to establish in natural communities or even become dominant. Since germination is the most critical stage in the life cycle of many plants, the influence of fire on seed dormancy breaking and germination may be decisive for the establishment of native (Reyes et al 2000) and invasive alien species (IAS) (Arán et al 2017). The ecological advantage of the non-dormant phase is that seeds can germinate abundantly in favorable conditions and establish large populations quickly.…”
Section: Introductionmentioning
confidence: 99%
“…Seed maturation can interact with fire and/or with summer temperatures (Luna 2020) by modulating the dormancy and germination response to fire (Reyes and Casal 2001;Ooi 2010). Specifically, Arán et al (2017) found that 2-year-old Acacia melanoxylon R. Br. seeds slightly increased germination compared with fresh seeds and that the seeds of the soil bank (many years of maturation) were mainly dormant seeds whose germination was stimulated by high fire temperatures, and García-Duro et al (2019) found great modifications of the viability, dormancy, and germination of Paraserianthes lophanta (Willd.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation